A numerical and experimental investigation of a special type of floating-slab tracks. (15th July 2020) - Alabbasi, Sateh; Hussein, Mohammed; Abdeljaber, Osama; Avci, Onur
Highlights: The dynamic behavior of a special type of Floating Slab Track (FST) is investigated. A fast running model for the special FST is developed based on the Dynamic Stiffness Method. A full-scale mockup track is studied experimentally and analytically. Model updating is conducted using an automated hybrid optimization technique. A parametric study is conducted to study the influence of grooves thickness on the dynamic behavior of the special track. Abstract: Floating-Slab Tracks (FST) are predominantly used for mitigating railway-induced vibrations where the concrete slab is mounted on soft resilient bearings to provide vibration isolation. This paper presents a research study on the dynamic behavior of a special type of FST used in the recently built subway system in Doha, Qatar. The special FST has a continuous concrete slab with periodic grooves. Therefore, the track can be modeled as a periodic structure with a slab unit having two elements with different cross-sections. Extensive numerical and experimental investigations were conducted on a multi-unit full-scale mockup track representing the special FST. A fast running model based on the Dynamic Stiffness Method was developed and examined, in an initial numerical exercise, against a detailed Finite Element model for a track with a finite length. In the experimental campaign, a test was performed with an impact hammer to identify the actual vibration response of the mockup track. Results from the experimental investigations were then used for model updating of the fast running model. The model updating process was carried out according to an automated hybrid optimization approach that combines genetic algorithms with a local search method. Finally, the updated model was extended to an infinite model to investigate the influence of varying grooves thickness on the dynamic behavior of the special track with infinite length for both bending and torsion scenarios. The investigations suggested that reducing the thickness below 50% of the full thickness of the slab significantly affects the dynamic behavior of the special FST.